2002
DOI: 10.1097/00129492-200207000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Increased Gentamicin Concentration for Intratympanic Injection Therapy in Ménière's Disease

Abstract: It was concluded that increasing the gentamicin concentration to 40 mg/ml probably produces similar rates of vertigo control as those of the lower dose, at least initially, but requires fewer injections. The higher dose did not increase the risk of hearing loss if treatment was stopped at the first indication of injury. A larger study is needed to confirm the trend of improved long-term hearing results in patients treated with the 40 mg/ml solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Although Abou-Halawa and Poe [7] have shown that 40 mg/ml is as effective as lower doses and requires fewer applications, we have chosen 30 mg/ml to remain on the safe side concerning possible cochlear damage and because application of gentamicin through a ventilation tube is not uncomfortable at all. In the gentamicin group both the scores for vertigo and aural fullness after 1 year were lower than at the start of the trial (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Although Abou-Halawa and Poe [7] have shown that 40 mg/ml is as effective as lower doses and requires fewer applications, we have chosen 30 mg/ml to remain on the safe side concerning possible cochlear damage and because application of gentamicin through a ventilation tube is not uncomfortable at all. In the gentamicin group both the scores for vertigo and aural fullness after 1 year were lower than at the start of the trial (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…A pair of high frequency transducers were coupled with the IHS system to generate specific acoustic stimuli that were presented at a rate of 37.1 per second. ABR thresholds were measured in response to toneburst stimuli with 1 ms rise/fall and 0 ms plateaus, gated by a Blackman envelope, and centered at frequencies of 4,8,12,16, and 32 kHz. Evoked potentials were band-pass-filtered between 30 and 3000 Hz.…”
Section: Auditory Assessmentmentioning
confidence: 99%
“…Although gentamicin is mainly toxic to the vestibule, ototoxicity is an important concern and can be encountered in up to 34% of the treated patients depending on the dose regimen and number of injections [1] . Different ITG application protocols have been described recently in order to achieve complete or substantial vertigo control with minimal risk of ototoxicity [2][3][4][5][6] . Despite these efforts, ITG is not an ideal treatment option for patients with serviceable hearing and/or bilateral MD.…”
Section: Introductionmentioning
confidence: 99%
“…The dosages and timing of therapy as well as endpoints selected to curtail therapy differ greatly among published reports (Youssef and Poe 1998, Minor 1999, Harner et al 2001, Abou-Halawa and Poe 2002, Chia et al 2004). In one series by Minor, 34 patients were evaluated in a protocol designed to determine clinical endpoints for cessation of intratympanic gentamicin therapy (Minor 1999).…”
Section: Medications Applied To the Middle Ear For Inner Ear Absorptionmentioning
confidence: 99%